Challenges of Diagnosing Primary Ewing’s Sarcoma in the Small Intestine of the Elderly: A Case Report - Yang, Jianchuan; Wei, Hong; Lin, Yucheng; Lin, Ning; Wu, Songsong; Yu, Xunbin (Frontiers in Oncology, 2021)
Extraosseous Ewing’s sarcoma (EES) is a malignant tumor that is classified as a rare disease. EES is common in children and adolescents, with a rarer incidence being present in the elderly. ES of the primary intestine is rare, with only a few reports described in the literature. Here we report a case of a 69-year-old male patient who was experiencing abdominal pain for over 3 months. Ultrasonography (US) revealed a solid hypoechoic lesion with multiple irregular necrotic areas in the left lower abdomen close to the dome of the bladder. Contrast-enhanced ultrasonography (CEUS) showed that the lesion exhibited heterogeneous enhancement and quick peripheral enhanced tissue wash-out classifying this mass as malignant. PET–CT showed a high metabolic mass in the lower abdomen, multiple metabolic nodules in the mesentery, considered as a small intestinal stromal tumor with lymph nodes metastasis, and that a diagnosis of lymphoma should be excluded. Esophagogastroduodenoscopy performed at another hospital 1 month prior to CT showed an abnormal density in the pelvic cavity that was considered as a colonic diverticulum with an abscess. The endoscopy showed no obvious occupying lesions. The mass was removed and postoperative pathology confirmed ES of the small intestine. The patient avoided receiving chemotherapy. After 2 months, skull metastasis was diagnosed and surgical intervention was done. His survival was only six months after the second surgery. To our knowledge, our case is the first report of ultrasound and CEUS manifestation of EES in the small intestine in elderly.